Applicability of extreme value distribution For analysis of rainfall over India - MUKHERJEE, K.; KAUR , SURINDER; MEHRA, A, K. (MAUSAM, 1991)
Applicability of extreme value type I distribution, for the analysis of annual maximum rainfall over, different parts of the country has been examined. It is observed that this distribution, function is generally applicable in major parts of the country except m the western parts where It has limited applicability, perhaps due to large variation rainfall.